Development of a Fish Feed and Water Control System for an Internet of Things-based Smart Aquarium - Cindy Tisni Permata; Asrizal; Yulkifli (Research on Instrumentation, 2025)
The cultivation of Discus ornamental fish requires a stable aquarium environment, particularly in maintaining water quality parameters such as temperature, pH, turbidity, and feeding management. Irregularities in these parameters can lead to stress, disease, and even mortality in fish. This study aims to design and implement an Internet of Things (IoT)-based Smart Aquarium system capable of monitoring and automatically controlling water quality and feeding in real time. The research method used is an engineering approach with experimental testing. The system is built using an ESP32 microcontroller integrated with a DS18B20 temperature sensor, pH sensor, turbidity sensor, and HX711 load cell sensor. The actuators include water pumps, relays, a heater, and a servo motor, supported by float switches and a water level sensor for automatic draining and refilling processes. System data is displayed through an I2C LCD and the Blynk application via Wi-Fi for remote monitoring. The experimental results show that the system operates effectively with high accuracy, where the temperature sensor achieves 99.45% accuracy, the pH sensor 98.51%, the turbidity sensor 99.30%, and the load cell sensor 99.25%. The system is capable of maintaining water temperature within the range of 28–30°C, detecting unsuitable water conditions, and controlling feeding based on weight automatically. Therefore, the proposed Smart Aquarium system improves efficiency, monitoring convenience, and the overall quality of Discus fish cultivation.